2009
DOI: 10.1038/aja.2008.33
|View full text |Cite
|
Sign up to set email alerts
|

Tumor formation of prostate cancer cells influenced by stromal cells from the transitional or peripheral zones of the normal prostate

Abstract: This study was designed to investigate the different involvements of prostatic stromal cells from the normal transitional zone (TZ) or peripheral zone (PZ) in the carcinogenesis of prostate cancer (PCa) epithelial cells (PC-3) in vitro and in vivo co-culture models. Ultra-structures and gene expression profiles of primary cultures of human prostatic stromal cells from the normal TZ or PZ were analyzed by electron microscopy and microarray analysis. In vitro and in vivo co-culture models composed of normal TZ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Based on our data the zonal origin of the inductive fibroblast is of less importance. Zhao et al showed that TZ fibroblasts inhibited the growth of androgen-independent PC-3 cells in vivo [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Based on our data the zonal origin of the inductive fibroblast is of less importance. Zhao et al showed that TZ fibroblasts inhibited the growth of androgen-independent PC-3 cells in vivo [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Stromal cells were separated from epithelial cells by discontinuous gradient centrifugation. 23 The stromal cells derived from the PZ (PZsc) and stromal cells derived from the TZ (TZsc) were identified by immunocytochemistry (IHC) 8 and cultured with RPMI 1640 supplemented with 10% foetal bovine serum (Gibco, Melbourne, Australia) and antibiotics (100 mg ml 21 streptomycin and 100 IU ml 21 penicillin) (Gibco BRL, Grand Island, NY, USA) at 37 uC under 5% CO 2 and a humidified atmosphere. The stromal cells were used at passages 3-5.…”
Section: Cell Culturementioning
confidence: 99%
“…Several studies have shown that the expression of certain genes differs between these two zones. [5][6][7][8][9] Feneley et al 10 reported that the epithelial content was significantly greater in the TZ than in the PZ. Conversely, concentrations of androgen receptor (AR) activity were higher in the PZ epithelium than in the TZ epithelium, but higher concentrations of oestrogen receptor activity were detected in the TZ zone stroma.…”
Section: Introductionmentioning
confidence: 99%
“…25 % of prostate cancer may arise from the central zone. Zhao F.J. et al, 7 noted in their study that there are morphological and ultra-structural differences in stromal cells from transitional zone (TZ) and peripheral zone (PZ) of the normal prostate. In all, 514 differentially expressed genes were selected by microarray analysis; 483 genes were more highly expressed in stromal cells IJBAR (2013) Most common metastasis associated with prostate cancer is skeletal metastasis spread through venous route.…”
Section: Discussionmentioning
confidence: 99%